School success, key to social inclusion in educational centers of San José, Costa Rica - Carpio Brenes, María de los Ángeles (2023)
This article shows the findings of an interdisciplinary study registered at the Educational Research Institute (INIE for its initials in Spanish), carried out by two researchers, one Guidance Counselor and one Special Educator, whose general objective was to analyze collaborative actions for the promotion of school success in four educational centers in San José, Costa Rica, in 2019. School success is understood here, not only as obtaining good grades, but as students’ holistic development (cognitive, socioaffective and psychomotor), and their full participation in the educational context as promoters of social inclusion. A qualitative study of phenomenological design was carried out, with the application of semi-structured interviews to professionals from the areas of I and II cycle of Basic General Education, Guidance and Special Education. The data was organized into three large categories, which resulted in: the identification of collaborative activities for the promotion of school success, contributions of each discipline in this joint work, and actions that promote students’ success. The study’s main conclusion is that the promotion of a holistic school success is highly pertinent and becomes more viable by means of collaborative work between professionals of the different disciplines.